“The Modern Father’s Role among Employed Fathers in Corporate Settings: A Case Study Approach” - Safariana, Astri Nur; Agustina, Laelatus Syifa Sari (Jurnal Psikologi, 2026)
Fathers traditionally were seen as providers of basic needs and did not play an active role in childcare. However, this has changed in recent decades. Fathers are now expected to contribute to many aspects of parenting. Hawkins in Inventory of Father Involvement describes the contemporary or “new father” role which consists of four dimensions; praise and affection, time and talking together, reading and homework support, and developing talents and future concerns. This research is important to conduct on working fathers as work demands exist as a challenge for them to fulfill the role of fathers in childcare. This study employed a case study method involving 14 participants (12=men, working fathers; 2=women, significant others). Based on thematic analysis with five major themes, it was found that fathers can fulfill the dimensions of “new father” role regardless of their busy work schedules. This finding has the potential to make good social change, especially for the government and companies in setting policies related to the need to fulfill the role of fathers in childcare. Deeper knowledge on father’s workplace flexibility and socioeconomic status is needed as determinants of the parenting quality. Exploring these dimensions will provide a deeper understanding of the variables that allow the 'new father' role to remain sustainable.